The efficacy of resiliency training programs: a systematic review and meta-analysis of randomized trials. - Aaron L Leppin; Pavithra R Bora; Jon C Tilburt; Michael R Gionfriddo; Claudia Zeballos-Palacios; Megan M Dulohery; Amit Sood; Patricia J Erwin; Juan Pablo Brito; Kasey R Boehmer; Victor M Montori (PLoS ONE)
Importance Poor mental health places a burden on individuals and populations. Resilient persons are able to adapt to life's challenges and maintain high quality of life and function. Finding effective strategies to bolster resilience in individuals and populations is of interest to many stakeholders. Objectives To synthesize the evidence for resiliency training programs in improving mental health and capacity in 1) diverse adult populations and 2) persons with chronic diseases. Data sources Electronic databases, clinical trial registries, and bibliographies. We also contacted study authors and field experts. Study selection Randomized trials assessing the efficacy of any program intended to enhance resilience in adults and published after 1990. No restrictions were made based on outcome measured or comparator used. Data extraction and synthesis Reviewers worked independently and in duplicate to extract study characteristics and data. These were confirmed with authors. We conducted a random effects meta-analysis on available data and tested for interaction in planned subgroups. Main outcomes The standardized mean difference (SMD) effect of resiliency training programs on 1) resilience/hardiness, 2) quality of life/well-being, 3) self-efficacy/activation, 4) depression, 5) stress, and 6) anxiety. Results We found 25 small trials at moderate to high risk of bias. Interventions varied in format and theoretical approach. Random effects meta-analysis showed a moderate effect of generalized stress-directed programs on enhancing resilience [pooled SMD 0.37 (95% CI 0.18, 0.57) p = .0002; I2 = 41%] within 3 months of follow up. Improvement in other outcomes was favorable to the interventions and reached statistical significance after removing two studies at high risk of bias. Trauma-induced stress-directed programs significantly improved stress [-0.53 (-1.04, -0.03) p = .03; I2 = 73%] and depression [-0.51 (-0.92, -0.10) p = .04; I2 = 61%]. Conclusions We found evidence warranting low confidence that resiliency training programs have a small to moderate effect at improving resilience and other mental health outcomes. Further study is needed to better define the resilience construct and to design interventions specific to it. Registration number PROSPERO #CRD42014007185.